Handbook of quantitative studies of science and technology - Raan, A. F. J. van (North-Holland ; Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1988)
Quantitative studies of science and technology represent the research field of utilization of mathematical, statistical, and data-analytical methods and techniques for gathering, handling, interpreting, and predicting a variety of features of the science and technology enterprise, such as performance, development, and dynamics. The field has both strongly developed applied research as well as basic research characteristics. The principal purpose of this handbook is to present this wide range of topics in sufficient depth to give readers a reasonably systematic understanding of the domain of con.